A Survey on Using Second-Life Batteries in Stationary Energy Storage Applications - Majid Gharebaghi; Omid Rezaei; Changyao Li; Zhanle Wang; Yili Tang (Energies)
As a key component of transportation decarbonization, the adoption of electric vehicles (EVs) is rapidly increasing. However, EV batteries are typically retired once their state of health drops to around 80%, usually after 10 to 20 years of use. Despite this decline, retired EV batteries still retain 70–80% of their original capacity. Reusing these retired batteries as second-life batteries (SLBs) for battery energy storage systems can offer significant economic and environmental benefits. This article provides a comprehensive analysis of the technical challenges and solutions, economic feasibility, environmental impacts, and case studies of existing projects. It also explores the current battery recycling process. The article concludes with an overview of the feasibility assessment, future development trends, market potential, and policy recommendations for the battery energy storage market.